Avaliação da intervenção farmacêutica na identificação e manejo de interações medicamentosas em uma Unidade de Terapia Intensiva - Santos, Tâmara Natasha Gonzaga de Andrade (2011)
Drug-drug interactions (DDI) represent a growing concern for the health units. Therefore, monitoring of pharmaceutical prescriptions in hospitals can rationalize pharmacotherapy. To evaluate the effect of pharmaceutical intervention in identifying and managing drug interactions in an intensive care unit (ICU), in Northeastern of Brazil. Methods: Initially, we performed a systematic review from the search of electronic databases, Jan. 1960 to Aug 2010. After that, we realized a longitudinal study in the ICU, in a private hospital in the city of Aracaju-SE, between 2008 and 2009, which was identified in the prevalence and clinical relevance of the DDI. During the study pharmaceutical interventions were aimed at the management of DDI. The systematic review, only seven articles met all inclusion criteria and the specific sample sizes ranged from 200 to 1785 patients. As for the longitudinal study, 6085 prescriptions were collected, of which 213 contained DDI clinically relevant. Of these 178 were moderate and 35 major severity. The clinical pharmacy interventions consisted in the preparation of reports for physicians, allowing the reduction of 40% of all DDI. The data obtained allow inferring that the participation of clinical pharmacists in the DDIs identification and management may have been essential to promote the safety of ICU patients.